Pram dan Cina - Hong, Liu; Mohamad, Gunawan, 1941-; Mandal, Sumit Kumar (Depok : Komunitas Bambu, 2008)
Account of Pramoedya Ananta Toer's opinions on Chinese descendant in Indonesia.
Pramoedya Ananta Toer dan Cina / Hong Liu -- Hoakiau di Indonesia / Goenawan Mohamad -- Orang asing yang tak asing / Sumit Kumar Mandal.
Mengandungi indeks.
Keywords: Toer, Pramoedya Ananta, -- 1925-2006.; Indonesian literature -- 20th century -- History and criticism; Chinese in literature